The Florida Mouse - Hannah H. Willingham; Emma V. Willcox; William M. Giuliano (EDIS, 2009)
WEC-362, a 3-page illustrated fact sheet by Hannah H. Willingham, Emma V. Willcox, and William M. Giuliano, describes this brownish to tawny colored rodent that lives in fire-maintained upland habitats in Florida — identification, habitat, distribution, behavior, conservation status, and habitat management. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, September 2009.